2014
DOI: 10.4236/jpee.2014.21001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of a Stand Alone Operation of PEM Fuel Cell System

Abstract: In this paper, the dynamic mathematical model of a proton exchange membrane (PEM) fuel cell is presented. Dynamic performance of a PEM fuel cell system by experimental and simulation using matlab/simulink is investigated. The V-I load characteristics of a 1.2 kW PEM fuel cell are presented. Result shows that the starting current of the PEM fuel cell operated at rated load reaches to approximately twice of its rated current in just less than 0.015 second before it reached to its steady state condition. Step cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…ܴ ௧ǡ and ܴ ǡ are activation and concentration losses of each single cell of PEMFC, respectively. They can be expressed as (7) and (8).…”
Section: ‫כ‬mentioning
confidence: 99%
See 1 more Smart Citation
“…ܴ ௧ǡ and ܴ ǡ are activation and concentration losses of each single cell of PEMFC, respectively. They can be expressed as (7) and (8).…”
Section: ‫כ‬mentioning
confidence: 99%
“…Several approaches are done to propose the static and dynamic model of PEMFC stacks [3]- [7] and [8] which provide the polarization curve (voltage as a function of current). In last few years, the numerical modeling, computer simulation and PEMFC stacks performance have been proposed [2], [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, optimization of the operating voltage is a crucial factor to enhance the electrochemical performance of the hybrid system. [54][55][56][57] The electrolytes used in Li-ion capacitors consist of lithium salts in organic solvents allowing for a large operating voltage. 58 It has been reported that a high cyclic stability is achieved by using a narrower voltage window at the cost of energy density.…”
Section: The Composition Of the Hybrid Supercapacitorsmentioning
confidence: 99%
“…The use of fuel cells is expected to mitigate environmental problems such as exhaustion of fossil fuels and greenhouse gas emissions. One type of fuel cell, the proton-exchange membrane fuel cell (PEMFC), has low operation temperature and exhibits rapid start-up; therefore, it is used in not only co-generation systems [1] but also fuel cell vehicles (FCVs) [2]. The widespread commercialization of PEMFC stacks depends on their reliability and fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%